Deconstruction of Patriarchal Construction: An Islamic Gender Analysis of Laysa Lahā Makān fī Al-Jannah: Tafkīk al-Binā’ al-Abawī: Dirāsah Jandariyyah Islāmiyyah li Riwāyat Laysa Lahā Makān fī al-Jannah - Cahaya, Shelinda (An-Nahdah Al-'Arabiyah, 2026)
This study aims to reveal how patriarchal culture manipulates Islamic values to legitimize the subordination of women and to reinterpret those values based on the principle of equality in the Qur’an. The study employs a qualitative descriptive method using library research, observation, and note-taking techniques. The theoretical framework applied is Asma Barlas’s Islamic feminism, which is grounded in the Qur’anic principle of equality. The results of the analysis show that patriarchal interpretations of Islamic concepts such as obedience, piety, and paradise function as mechanisms of social control that are internalized by female characters, affecting both their bodies and consciousness. The novelty of this research lies in its deconstructive reading based on Islamic gender theory, which emphasizes that gender inequality in the text does not originate from the Qur’an itself, but rather from patriarchal interpretations that deviate from its ethical vision.   يهدف هذا البحث إلى الكشف عن كيفية توظيف الثقافة الأبوية للقيم الإسلامية من أجل إضفاء الشرعية على إخضاع المرأة، وإعادة تفسير هذه القيم استنادًا إلى مبدأ المساواة في القرآن الكريم. يعتمد هذا البحث على المنهج الوصفي النوعي من خلال الدراسة المكتبية، والملاحظة، وتقنية تدوين الملاحظات. ويستند الإطار النظري المعتمد إلى النسوية الإسلامية لدى أسماء برلاس، القائمة على مبدأ المساواة القرآني. وتُظهر نتائج التحليل أن التفسيرات الأبوية للمفاهيم الإسلامية مثل الطاعة، والتقوى، والجنة، تؤدي وظيفة آليات للضبط الاجتماعي يتم استبطانها من قِبل الشخصيات النسائية، مما يؤثر في أجسادهن ووعيهن على حد سواء. وتكمن جدة هذا البحث في قراءته التفكيكية القائمة على نظرية الجندر الإسلامية، التي تؤكد أن عدم المساواة الجندرية في النص لا تنبع من القرآن ذاته، وإنما من التفسيرات الأبوية التي تنحرف عن رؤيته الأخلاقية.   Penelitian ini bertujuan untuk mengungkap bagaimana budaya patriarki memanipulasi nilai-nilai keislaman untuk melegitimasi subordinasi perempuan serta menafsirkan ulang nilai-nilai tersebut berdasarkan prinsip kesetaraan dalam Al-Qur’an. Penelitian ini menggunakan metode deskriptif kualitatif dengan teknik pustaka, simak, dan catat. Kerangka teoritis yang digunakan adalah feminisme Islam Asma Barlas yang berangkat dari prinsip kesetaraan dalam Al-Qur’an. Hasil analisis menunjukkan bahwa penafsiran patriarkal atas konsep-konsep keislaman seperti ketaatan, kesalehan, dan surga berfungsi sebagai mekanisme kontrol sosial yang diinternalisasi oleh tokoh perempuan, baik terhadap tubuh maupun kesadarannya. Kebaruan penelitian ini terletak pada pembacaan dekonstruktif berbasis gender Islam yang menegaskan bahwa ketimpangan gender dalam teks bukan bersumber dari Al-Qur’an, melainkan dari tafsir patriarkal yang menyimpang dari visi etisnya.